Growth And Production Of Seaweed Caulerpa Lentillifera With Microorganism Liquid Organic Fertilization Local (MOL) From bean Sprouts - Safitri, Nur Annisa; Darmawati, Darmawati; Khaeriyah, Andi; Sambu, Abdul Haris; Wahyu, Farhanah (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Caulerpa lentillifera seaweed is one of the seaweed commodities that is very popular with the community, it has even been produced through aquaculture. Caulerpa lentillifera seaweed has a fairly high nutritional content in the form of carbohydrates, proteins, vitamins, and minerals. Increased production can be done by developing cultivation technology, namely by giving liquid organic fertilizer as a stimulant in accelerating growth. This study aims to determine the concentration of liquid organic fertilizer from bean sprouts to increase the growth and production of Caulerpa lentillifera seaweed. The research method used a completely randomized design (CRD) with 4 treatments and 3 replications. Treatments A, B, C, and D (each given MOL: 1.5 mL MOL/L water, 2 mL MOL/L water, 2.5 mL MOL/L water, and 3 mL MOL/L water). Data analysis using ANOVA and continued Duncan's test. The results showed that the application of liquid organic fertilizer to Caulerpa lentillifera seaweed using 3 mL MOL/L of local microorganism water from bean sprouts gave the highest absolute growth of 374 g and the highest production of 3.74 kg/m2.